Evaluation of Peruvian Government Interventions to Reduce Childhood Anemia - Axel J. Berky; Emily Robie; Ernesto J. Ortiz; Joel N. Meyer; Heileen Hsu-Kim; William K. Pan (Ubiquity Press, 2020)
Background: In Peru, anemia has been a persistent health problem that is known to lead to irreversible cognitive and developmental deficits in children. The Peruvian government has recently made anemia a primary health concern by passing legislation in 2017 that makes anemia an intersectoral priority. This new legislation fortifies previous programs while creating new programs that target specific age groups. Objectives: Evaluate the effectiveness of government programs in Madre de Dios, Peru to reduce anemia prevalence and increase hemoglobin levels among children ages 2-11 years old. Methods: Propensity scores are used to match 688 children enrolled in 2018, after the legislation, and 2,140 children enrolled in previous studies our team conducted in the region between 2014 and 2017, based on sex, age (years), intervention status (prior/post), community income, presence of a health post in the community (yes/no), community type (indigenous, non-indigenous rural, non-indigenous urban) and road access (fraction of the number of months out of the year with road access). A pseudo matched case-control analysis to evaluate changes in anemia prevalence and hemoglobin was conducted using t-tests and multivariate models. Program effectiveness is evaluated overall, by age groups (2-4, 5-7 and 8-11 years old), and community type (indigenous vs. urban). Findings: The adjusted odds ratio indicated lower odds of anemia (OR = 0.31, 95%CI 0.17-0.54) for children exposed to the anemia prevention programs vs. those not exposed. The effect was not significantly different across age groups; however, the intervention effects significantly differed by community type among children 8-11 years old, with urban children less likely to benefit from anemia interventions (OR = 0.69, 95% CI 0.38-1.25) compared to indigenous children (OR = 0.21, 95% CI 0.08-0.56). Conclusion: Government programs to reduce anemia in Madre de Dios were found to be associated with reduced anemia prevalence in the study communities. However, the lack of program monitoring precludes the attribution of anemia decline to specific interventions or program components. In addition, regional anemia prevalence remains high according to the 2019 Demographic and Health Survey, suggesting impaired population impact. Program monitoring and evaluation is a key component of health interventions to improve program implementation effectiveness.